2021
DOI: 10.1093/nar/gkab002
|View full text |Cite
|
Sign up to set email alerts
|

Super-enhancer mediated regulation of adult β-globin gene expression: the role of eRNA and Integrator

Abstract: Super-enhancers (SEs) mediate high transcription levels of target genes. Previous studies have shown that SEs recruit transcription complexes and generate enhancer RNAs (eRNAs). We characterized transcription at the human and murine β-globin locus control region (LCR) SE. We found that the human LCR is capable of recruiting transcription complexes independently from linked globin genes in transgenic mice. Furthermore, LCR hypersensitive site 2 (HS2) initiates the formation of bidirectional transcripts in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…In accordance with this scenario, a number of studies have demonstrated that the same transcription factors are present both on the enhancer and on the promoters of genes controlled by this enhancer [35][36][37]. Due to the higher density of binding sites for transcription factors on enhancers, it is the enhancers that serve as the nucleation centers for the assembly of activator compartments [38][39][40]. The attraction of promoters to the activator compartment is controlled by architectural proteins.…”
Section: Erythroid-specific Genesmentioning
confidence: 86%
“…In accordance with this scenario, a number of studies have demonstrated that the same transcription factors are present both on the enhancer and on the promoters of genes controlled by this enhancer [35][36][37]. Due to the higher density of binding sites for transcription factors on enhancers, it is the enhancers that serve as the nucleation centers for the assembly of activator compartments [38][39][40]. The attraction of promoters to the activator compartment is controlled by architectural proteins.…”
Section: Erythroid-specific Genesmentioning
confidence: 86%
“…When transcribed, they stay present at the gene locus and upon their depletion a reduction in gene expression was observed, as well as an accumulation of PolII at the LCR. [ 3 ] A similar mechanism has been suggested to activate gene expression at promoters. Paraspeckle promoting protein PSPC1 (an RNA binding protein found in paraspeckles, a type of condensate) was shown to bind RNA at sites of transcription initiation, contributing to recruitment of PolII.…”
Section: Ernasmentioning
confidence: 91%
“…[3,4] When the Integrator endonuclease subunit INTS11 was depleted in murine erythroleukemia (MEL) cells, an accumulation of PolII was observed at the locus control region (LCR) of β-globin and decreased recruitment to the promoter of β-globin, highlighting the importance of Integrator in PolII release and transfer. [3] Similar observations were apparent upon acute, degron-mediated depletion of INTS11 in mouse embryonic stem cells (mESCs), where depletion of INTS11 caused a build-up of PolII at promoters and accumulation of short RNA transcripts, including eRNAs. [4] In this study, transferred PolII was shown to be predominantly unphosphorylated, with the phosphatase subunit of Integrator being transferred along with PolII.…”
Section: Enhancers Super Enhancers and Lcrsmentioning
confidence: 99%
“…Although eRNAs are generally less stable than mRNAs, their average half-life ranges from 5 to 10 min. The relatively short half-life suggests that eRNA function is transient [ 47 , 48 ].…”
Section: The Role Of Enhancer Transcription and Ernamentioning
confidence: 99%